2015
DOI: 10.1016/j.physbeh.2015.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Lipid transport in cholecystokinin knockout mice

Abstract: Cholecystokinin (CCK) is released in response to lipid feeding and regulates pancreatic digestive enzymes vital to the absorption of nutrients. Our previous reports demonstrated that cholecystokinin knockout (CCK-KO) mice fed a 10 weeks of HFD had reduced body fat mass, but comparable glucose uptake by white adipose tissues and skeletal muscles. We hypothesized that CCK is involved in energy homeostasis and lipid transport from small intestine to tissues in response to acute treatment with dietary lipids. CCK-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 96 publications
(126 reference statements)
1
11
0
Order By: Relevance
“…Moreover, CCK‐8 effects appeared to be insulin‐dependent and, in the case of subcutaneous WAT, linked to the activation of PPARγ. Taken together, our findings support the concept, already suggested by previous studies carried out by our group and others (King, Yang, Huesman, Rider, & Lo, ; Plaza, Merino, Cano, et al, ; Plaza, Merino, Sánchez‐Pernaute, et al, ), that both CCK and CCK binding sites have a relevant role in modulating WAT homeostasis, particularly in the case of Sc‐WAT.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, CCK‐8 effects appeared to be insulin‐dependent and, in the case of subcutaneous WAT, linked to the activation of PPARγ. Taken together, our findings support the concept, already suggested by previous studies carried out by our group and others (King, Yang, Huesman, Rider, & Lo, ; Plaza, Merino, Cano, et al, ; Plaza, Merino, Sánchez‐Pernaute, et al, ), that both CCK and CCK binding sites have a relevant role in modulating WAT homeostasis, particularly in the case of Sc‐WAT.…”
Section: Discussionsupporting
confidence: 92%
“…This regulation would be accomplished by: (i) limiting food intake; (ii) delaying gastric emptying; (iii) facilitating intestinal digestion of fat and TG absorption and (iv) enhancing fatty acid (FA) catabolism in oxidative tissues. More recently, King and coworkers demonstrated that FA uptake by adipose tissue in CCK-knockout mice is impaired (King et al 2015, Weng et al 2017. In a recent study, Demenis et al (2017) reported that CCK-8 promotes CD-36-mediated FA uptake by mouse enterocytes.…”
Section: Introductionmentioning
confidence: 99%
“…The proposition that CCK induces an increase in enterocyte FA to facilitate nutrient absorption is supported by reported findings in CCK-KO mice (King et al, 2015 ). In response to acute intraduodenal introduction of lipids mice lacking CCK were observed to have delayed secretion of Apo B48-chylomicrons and lipid transport to the lymphatic system.…”
Section: Discussionmentioning
confidence: 63%
“…In response to acute intraduodenal introduction of lipids mice lacking CCK were observed to have delayed secretion of Apo B48-chylomicrons and lipid transport to the lymphatic system. Both of these effects are indicative of impaired FA uptake into enterocytes compared to wild type animals and support a physiological role for CCK-induced lipid absorption (King et al, 2015 ).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation